PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PENIPUAN DENGAN MODUS MENGGADAIKAN KENDARAAN RODA EMPAT - Hartono, Bambang; Anita, Okta; Hermawan , Hengki (Universitas Wiralodra, 2024)
ABSTRACT The perpetrators of crimes vary from ordinary people to law enforcement officers who are the main actors in a crime. One of the crimes or crimes that often occur in society is the crime of fraud. One example of a criminal act of fraud using the mode of pawning a four-wheeled vehicle is in Decision Number: 127/Pid.B/2022/PN Gns with the defendant I Gusti Ngurah Toni Efendi, son of I Gusti Komang Suardika and the victim Sukari and the scene of the incident in Kampung Rukti Endah Dusun III Seputih Raman District, Central Lampung Regency. The research method uses a normative and empirical juridical approach. Normative and empirical data sources. Data collection through library research and field research. The data analysis used is qualitative juridical. Based on the results of the research, it is known that the factors that cause perpetrators to commit criminal acts of fraud by pawning four-wheeled vehicles are the factors that cause perpetrators to commit criminal acts of fraud by pawning four-wheeled vehicles is the factor of meeting their daily living needs, they have no other way except criminal acts of fraud. by pawning four-wheeled vehicles even though the legal risks are serious.